Congenital Syngnathia; Turmoils and Tragedy - Sarin, Yogesh Kumar; Raj, Prince; Arya, Mona; Dali, Jaspal Singh (Journal of Neonatal Surgery, 2016)
Congenital syngnathia is an extremely rare condition with no standardized treatment. We hereby report a case highlighting the difficulties faced in its management and the postoperative complications.